2004
DOI: 10.1007/s00330-003-2212-1
|View full text |Cite
|
Sign up to set email alerts
|

MRI of slow flow in artificial duct in swine

Abstract: Our aim was to evaluate whether it is possible to visualize slow flow within a small catheter placed inside a living animal. We used a flow-sensitive, single-shot turbo spin-echo (SS-TSE) MRI sequence, developed in house, based on diffusion-weighted (DW) techniques. Four anesthetized pigs were used as models. A plastic catheter was surgically placed within the common bile duct (CBD). To mimic flow, the catheter was filled with Ringer's acetate and connected to a pump. b factors (s/m(2)) of 0, 6, and 12, with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Initial tests in an experimental study showed that semi-quantitative evaluation of flow was possible (6). This paper presents the first results in humans, using healthy volunteers.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Initial tests in an experimental study showed that semi-quantitative evaluation of flow was possible (6). This paper presents the first results in humans, using healthy volunteers.…”
Section: Discussionmentioning
confidence: 96%
“…The MRI sequences have been presented previously (Fig. 1) (5,6). A Phillips Gyroscan ACS-NT (1.5T; Best, The Netherlands) with Powertrack 6000 gradient system was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this technique is not physiologic because it requires the injection of secretin. Other reports have suggested that pancreatic juice fl ow could be detected by using a single-shot turbo spin-echo sequence based on a diffusion-weighted MR imaging technique (18)(19)(20). In this approach, the stationary pancreatic fl uid appears bright, while the moving pancreatic fl uid loses signal intensity as the b value used increases and appears as a fl ow void.…”
Section: Discussionmentioning
confidence: 97%
“…As another method to assess the pancreatic juice movement, Hellund et al (20, 21) reported that diffusion‐based sequence could detect pancreatic juice flow. However, their method showed visualization of pancreatic juice movement indirectly as a flow void.…”
Section: Discussionmentioning
confidence: 99%